Critical Issues in Head and Neck Oncology Key Concepts from the Seventh THNO Meeting - Vermorken, Jan B.; Budach, Volker; Leemans, C. René; Machiels, Jean-Pascal; Nicolai, Piero; O'Sullivan, Brian (Springer Nature, 2021)
This open access book discusses the most current issues in head and neck cancer with a focus on current trends such as biomarkers, precision medicine and immunotherapy. New approaches in the diagnosis such as liquid biopsies and imaging biomarkers to predict radiotherapy toxicity as well as approaches in the surgical management of head and neck cancers are discussed. The book discusses medical and surgical approaches in both primary, recurrent and metastatic disease and also covers approaches for rare head neck cancers. Readers will learn about the latest drug developments and epidemiological aspects in cancers ranging from Head and Neck Squamous Cell Cancer to Nasopharynx cancer. Edited by a team of world leaders in Head and Neck Cancer, this volume serves as an easy reference to the head and neck oncology practitioner and provides a contemporary overview for specialists the field. The chapters are based on the latest data presented at the 7th Trends in Head and Neck Oncology Conference and reflect the most up-to-date information in the field.